The Effect of Team Assisted Individualization (TAI) Model and Project Based Learning (PJBL) on Learning Outcomes of Interactive Media Design Subjects of Vocational Students - Siti Mutoharoh; Rahmania Sri Untari; Cindy Cahyaning (International Consortium of Education and Culture Research Studies, 2020)
The study aims to know difference before and after applying of Team Asisted Individualization ( TAI) and of Project learning based ( PJBL) to result learn student. Research [done/conducted] [by] [in] SMKN 1 BEJI with class subjek of XI and multimedia1 of XI multimedia 3.. This research use quantitative research method with type research of Quasi Experiment ( Eksprimen Design) with Desain Nonequivalent Control Group Design. used Device [at] this research represent Control Group design posttest pretest. Technique data collecting use sheet of tes that is and pretest of posttest. Technique analyse data use to [count/calculate] normalitas,dan rata-rata,uji test Paired Sample Test. Result of from calculation of mean obtain;get class value of Eksprimen 79 and class Control 72. While data collecting technique use Test of Paired Sampel T-Tes result of research cover influence of Applying Of Model of Team Assisted Individualization ( TAI) and of Project Based Learning ( PJBL) with value of Signifikasi 0,00 < 0,05. While [at] result of test of Paired Sampel T-Tes influence of applying of model of Team Assisted Individualization ( TAI) and of Project Based Learning ( PJBL) prove that with value of signifikasi 0,00. Pursuant to data analysis to result of this research can be said that [by] result learn student there are difference before and after using Model of Team Assisted Individualization ( TAI) and of Project Based Learning ( PJBL) Subject of desain media of interaktif class of XI multimedia.